Differentiating Suicide Attempters from Suicide Ideators: The Role of Capability for Suicide. Issue 1 (2nd January 2019) - Ren, Yaxuan; You, Jianing; Zhang, Xu; Huang, Jiyi; Conner, Bradley T.; Sun, Rui; Xu, Sian; Lin, Min-Pei
Abstract : This study examined whether different components of capability for suicide (i.e., fearlessness about death, pain tolerance, pain insensitivity, preparation for suicide, suicide plan, and courage), as well as painful and provocative events, nonsuicidal self-injury, depressive symptoms, and hopelessness, could distinguish between suicide attempters, suicide ideators, and non-suicidal controls. A total of 930 Chinese adolescents completed questionnaires, and a multinomial logistic regression was conducted to identify factors that could distinguish among the 3 groups. We found that higher levels of pain tolerance, more detailed suicide plans, more positive attitudes towards suicide, as well as more painful and provocative experiences and more severe depressive symptoms were positively associated with increased likelihood of the engagement in both suicide ideation and suicide attempts. Only nonsuicidal self-injury increased the likelihood of falling in the suicide attempt group as compared to the suicide ideation group. Findings of this study emphasize the role of nonsuicidal self-injury in intervening suicidality.